Alleviation of Lipopolysaccharide-Induced Acute Respiratory Distress Syndrome in Rats by Yiqi Huayu Jiedu Decoction: A Tandem Mass Tag-Based Proteomics Study - Luo, Chang-yong; Li, Yan; Li, Xin; Liang, Xu; Wang, Qian; Ma, Yuan-hong; Xiong, Cai-hua; Zeng, Yan-peng; Sun, Wei; Wang, Xin (Frontiers in Pharmacology, 2020)
Background: To study the effect of Yiqi Huayu Jiedu Decoction (YQHYJD) on protein expression in the lung tissue of acute respiratory distress syndrome (ARDS) rats and to explore the underlying molecular therapeutic mechanism of YQHYJD. Methods: Sprague Dawley rats were administered with YQHYJD by oral gavage for 1 week. The rats were injected with lipopolysaccharide (LPS) to induce ARDS. The lung injury was assessed pathologically. Differentially expressed proteins (DEPs) were screened by quantitative proteomics and analyzed using bioinformatic tools, such as Metascape and Kyoto Encyclopedia of Genes and Genomes (KEGG) mapper. DEPs were verified by parallel reaction monitoring (PRM). Results: YQHYJD alleviated the LPS-induced pathological damage of lung tissue in rats. There were 134 DEPs among the YQHYJD treatment and model groups. The Genomes pathway analyses revealed that the DEPs were closely related to immune system pathway. The mass spectrometry analysis revealed that YQHYJD exhibits a protective effect on lung tissue by significantly upregulating hematopoietic cell kinase (Hck), phospholipid phosphatase 3 (Plpp3), myristoylated-alanine rich C-kinase substrate (Marcks) and Actin-related protein 2/3 complex subunit 2 (Arpc2), which are related to Fc gamma receptor-mediated phagocytosis pathway. Conclusion: YQHYJD can alleviate the lung injury of ARDS rats by regulating the Fc gamma receptor-mediated phagocytosis pathway, which are related to immune system.